PPP2CA knockdown upregulates the expression levels of ferroptosis-related genes TFRC and ACSL4 in colorectal cancer cells by promoting mTOR phosphorylation - Cheng, Jing; Liu, Zhihan; Liu, Haibo; Fang, Chao; Li, Jun (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is one of the most prevalent malignant tumors worldwide, with its pathogenesis tightly linked to the regulation of cell death. Ferroptosis plays a pivotal role in the initiation, progression, and treatment of CRC. In our previous studies, we demonstrated that PPP2CA knockdown enhances the malignant phenotype of CRC cells while increasing their susceptibility to ferroptosis, albeit this latter effect frequently mitigates the malignant phenotype. The present study aims to further elucidate the regulatory mechanism underlying the association between PPP2CA and ferroptosis.​ Lentiviral-mediated PPP2CA knockdown was performed in CRC cell lines HCT116 and SW480 to establish stable PPP2CA-knockdown models, and PPP2CA gene expression in these models was verified. Colony formation assays and scratch wound healing assays were used to assess the proliferative and migratory capacities of CRC cells after PPP2CA knockdown. Additionally, CRC samples from The Cancer Genome Atlas (TCGA) database were analyzed via bioinformatics approaches to identify ferroptosis-related genes closely correlated with PPP2CA, with subsequent validation in model cells. The STRING database was employed to analyze the interaction networks between PPP2CA and target ferroptosis-related genes, predict potential signaling pathways via which PPP2CA regulates cellular ferroptosis, and validate these findings in model cells.​ Compared with the control group, HCT116 and SW480 cells in the PPP2CA-knockdown group exhibited significantly enhanced proliferative and migratory capacities. Bioinformatics analysis identified the top 10 most significant ferroptosis-related genes associated with PPP2CA. Validation in model cells showed that the expression levels of transferrin receptor (TFRC) and acyl-CoA synthetase long-chain family member 4 (ACSL4) were significantly upregulated. STRING analysis and in-model-cell validation indicated that increased mTOR phosphorylation subsequent to PPP2CA knockdown could upregulate the protein expression levels of transferrin receptor (TfR, encoded by the TFRC gene) and ACSL4, and this effect could be reversed by the mTOR inhibitor rapamycin.​ Thus, PPP2CA knockdown enhances the malignant phenotype of CRC cells, while potentially upregulating the expression of ferroptosis-related genes TFRC and ACSL4 via the mTOR signaling pathway, thereby increasing ferroptosis sensitivity.